The MTP1 promoters from Arabidopsis halleri reveal cis‐regulating elements for the evolution of metal tolerance. Issue 4 (23rd March 2017) - Fasani, Elisa; DalCorso, Giovanni; Varotto, Claudio; Li, Mingai; Visioli, Giovanna; Mattarozzi, Monica; Furini, Antonella
Summary: In the hyperaccumulator Arabidopsis halleri, the zinc (Zn) vacuolar transporter MTP1 is a key component of hypertolerance. Because protein sequences and functions are highly conserved between A. halleri and Arabidopsis thaliana, Zn tolerance in A. halleri may reflect the constitutively higher MTP1 expression compared with A. thaliana, based on copy number expansion and different cis regulation. Three MTP1 promoters were characterized in A. halleri ecotype I16. The comparison with the A. thaliana MTP1 promoter revealed different expression profiles correlated with specific cis ‐acting regulatory elements. The MTP1 5′ untranslated region, highly conserved among A. thaliana, Arabidopsis lyrata and A. halleri, contains a dimer of MYB‐binding motifs in the A. halleri promoters absent in the A. thaliana and A. lyrata sequences. Site‐directed mutagenesis of these motifs revealed their role for expression in trichomes. A. thaliana mtp1 transgenic lines expressing AtMTP1 controlled by the native A. halleri promoter were more Zn‐tolerant than lines carrying mutations on MYB‐binding motifs. Differences in Zn tolerance were associated with different distribution of Zn among plant organs and in trichomes. The different cis ‐acting elements in the MTP1 promoters of A. halleri, particularly the MYB‐binding sites, are probably involved in the evolution of Zn tolerance.